2015
DOI: 10.1016/j.gdata.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of HOXA9-regulated genes in human glioblastoma cell models

Abstract: The data here described pertain to the article by Pojo et al. (2015) [10] titled “A transcriptomic signature mediated by HOXA9 promotes human glioblastoma initiation, aggressiveness and resistance to temozolomide” (Pojo et al., 2015 [10]). HOX genes are part of the homeobox gene family, which encodes transcription factors crucial during embryonic development (Grier et al., 2005; Pearson et al., 2005 [6], [9]) and also in postdevelopmental regulation (Neville et al., 2002; Yamamoto et al., 2003; Takahashi et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Previously published transcriptomic data from our group (GEO accession number GSE56517) [ 26 , 27 ] suggested a possible regulation of HOTAIR by the homeoprotein HOXA9, an important protein in the aggressiveness, chemotherapy resistance, and prognosis of GBM [ 21 , 26 , 28 , 29 ]. Specifically, GBM cell lines with overexpression or silencing of HOXA9 presented increased or reduced expression of HOTAIR , respectively; raising the hypothesis that HOXA9 may directly regulate HOTAIR expression.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published transcriptomic data from our group (GEO accession number GSE56517) [ 26 , 27 ] suggested a possible regulation of HOTAIR by the homeoprotein HOXA9, an important protein in the aggressiveness, chemotherapy resistance, and prognosis of GBM [ 21 , 26 , 28 , 29 ]. Specifically, GBM cell lines with overexpression or silencing of HOXA9 presented increased or reduced expression of HOTAIR , respectively; raising the hypothesis that HOXA9 may directly regulate HOTAIR expression.…”
Section: Resultsmentioning
confidence: 99%
“…expression in clinical specimens of ovarian cancer was strongly associated with increased abundance of tumor-associated macrophages (TAMs) and intratumoral T-regulatory cells [22]. Céline S. Gonçalves et al as well as Marta Pojo et al identifed HOXA9 as a critical oncogene in the initiation and progression of glioma that establish HOXA9 as a driver of glioma initiation, aggressiveness and resistance to therapy [23,24]. John Wrangle et al de ned a three-gene panel, CDO1, HOXA9, and TAC1, which degree of sensitivity and speci city may be of high value to diagnose the earliest stages of NSCLC [25].…”
Section: Discussionmentioning
confidence: 99%
“…Further chromatin immunoprecipitation analysis (ChIP) revealed the direct interaction between HOXC8 and the osteopontin promoter (OPN) and, subsequently, reduced OPN expression, confirming that OPN is a HOXC8 direct target [30]. Similarly, other authors have shown that HOXA9 overexpression is able to induce the expression of genes associated with the establishment of typical stemness characteristics, such as invasive potential, migration, etc., properties that can be reverted after HOXA9 silencing [31]. Collectively, these pieces of evidence seem to indicate that OA-MSCs have a partial loss of their stemness and simultaneously adopt a phenotype with typical characteristics of bone tissue.…”
Section: Discussionmentioning
confidence: 99%